Everything you always wanted to know about Bakhtin (but were afraid to ask Groys): Pop culture and the persistence of hieratic senses - Gómez Ponce, Fernando Ariel (2024)
This article examines the intersection of Boris Groys’ and Mikhail Bakhtin’s cultural theories, with the aim of elucidating how the concept of carnivalization informs Groys’ thought. It argues that engaging in a dialog between these two thinkers provides a framework for understanding pop culture as a significant place where market forces, consumer society, and mass media interact in complex ways, challenging traditional theoretical perspectives. The article reaches such an interpretation, suggesting that Bakhtin proposes a secularized view of popular culture, where meaning-making retains traces of religious significance. This hieratic dimension, marked by the persistence of fetishistic and cult practices, is also observed by Groys in his analysis of contemporary media culture, which is imbued with ritualistic and cultic imagery. Through documentary analysis and critical interpretation, the article contends that the ecstatic dissolution of individuality and the enduring sacredness of icons are key features of current pop culture, where a strong semiotic dynamic drives the continual mutation and transformation of signs. The conclusions highlight the importance of Bakhtin’s influence on Groys’ thought and his concept of carnivalization, proposing further research into its implications for the study of pop culture.